THE COMMITMENT ANALYSIS OF RELIGION MINISTRY IN BANTEN PROVINCE - Mukrodi, Mukrodi (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
The purpose of this study is to determine the influence of Organizational Culture and Motivation against Employee Commitment at the Ministry of Religion Banten Province. The research design used in the preparation of this study is quantitative causal associative with descriptive explanation. The analysis method used is multiple linear regression analysis with sample of 59 and sampling technique used is simple random technique. The test results prove that organizational culture has a positive and significant effect on Employee Commitment with regression coefficient value of 0,462. Work motivation has a positive and significant effect on Employee Commitment with the value of regression coefficient of 0,612. Simultaneously proved organizational culture and work motivation positive and significant to Employee Commitment with determination coefficient equal to 89,7%. While the remaining 10.3% is explained by other variables outside this study, such as leadership, career, work environment, competence and others